Interposition Arthroplasty for Posttraumatic Ulnohumeral Arthritis. (March 2019) - Blaine, Theodore A; Wiseman, Stephen P; Kovacevic, David; Morrey, Bernard F
Posttraumatic elbow arthritis presents a difficult problem in young patients. Total elbow arthroplasty may not be suited to the functional demands placed on the prosthesis in younger, more active individuals. Interposition arthroplasty is a useful nonprosthetic alternative in these patients. Various biologic materials have been employed as an interpositional graft, with Achilles tendon allograft being the preferred material. Successful outcomes have been reported in 26% to 94% cases, with the best results in patients with posttraumatic arthritis with stiffness and no underlying instability. Poor prognostic factors associated with this procedure include malalignment and pre- and postoperative instability. Use of a hinged-distraction device to allow immediate postoperative range of motion while protecting the graft may further improve results. In those patients where postoperative instability occurs or where results deteriorate with time, stability and pain relief can be salvaged by conversion to a semiconstrained total elbow arthroplasty.